Organizational change in the US Forest Service: negotiating organizational boundaries in the collaborative process - Orth, Patricia B., author; Cheng, Antony S., author; Springer Nature, publisher (Colorado State University. Libraries, 2019)
In the United States and across the globe, forest governance officials are seeing a rise in the demand from local community members to participate in forest management decision-making. Despite this demand, there have been few studies that seek to describe the impact of community collaborative efforts on the organizational structures and processes of governmental forest management agencies. We empirically examined the boundary negotiations occurring at the field office level of the United States Forest Service in order to understand organizational change with respect to the collaborative process. We employed a qualitative case study approach encompassing the examination of three community collaborative groups. By examining the defining characteristics of organizational boundaries, we found that boundary negotiations are facilitating organizational change through individual-level learning and behavior changes. We present data suggestive of negotiations for boundaries of knowledge, responsibility, and capacity. Understanding the organizational outcomes of community collaboration will help forest managers respond and adapt to changing forest management strategies.
Keywords: organizational change; collaboration; United States Forest Service; natural resources management; boundaries; boundary negotiation